Alterations in the Corneal Nerve and Stem/Progenitor Cells in Diabetes: Preventive Effects of Insulin-Like Growth Factor-1 Treatment. (18th February 2014) - Ueno, Hiroki; Hattori, Takaaki; Kumagai, Yuta; Suzuki, Noboru; Ueno, Satoki; Takagi, Hitoshi
Abstract : This study aimed to investigate whether corneal nerve and corneal stem/progenitor cells are altered in insulin-like growth factor-I (IGF-I-) treated individuals with diabetes. A group consisting of db/db mice with type 2 diabetes mellitus (DM) and a wild-type group were assessed by neural and corneal stem/progenitor cell markers immunostaining and real-time PCR. Moreover, the expression of corneal nerve and stem/progenitor cell markers was examined in IGF-1-treated diabetic mice. Compared with a normal cornea, swelling and stratification of the corneal epithelium were noted in db/db mice. Beta-III tubulin immunostaining revealed that the corneal subbasal plexuses in diabetic mice were thinner with fewer branches. mRNA expression levels of Hes1, Keratin15, and p75 (corneal stem/progenitor cell markers) and the intensity and number of positive cells of Hes1 and Keratin19 immunostaining diminished in the diabetic corneas. Compared with the subbasal nerve density in the normal group, a decrease in the diabetic group was observed, whereas the corneal subbasal nerve density increased in IGF-1-treated diabetic group. The decreased expression of Hes1 and Keratin19 was prevented in IGF-1-treated diabetic group. Our data suggest that corneal nerve and stem/progenitor cells are altered in type 2 DM, and IGF-I treatment is capable of protecting against corneal damage in diabetes.